A simulation study of photovoltaic modelling for DC-DC converter system - A’azimah, Sa’adon Zubir (2016)
Photovoltaic (PV) cells convert sunlight directly to electricity. There are two critical parameters that affect the output of PV cells that are temperature of PV cells and irradiance. The DC-DC converter converts dc voltages to different dc voltage level and provide regulated output. In this project an equivalent PV module are modelled in Matlab Simulink environment to test the effect of PV cells temperature and irradiance to the PV module output. The PV module mathematically modelled to calculate the current of PV module and feed into controlled current source to add electric port to create physical model of PV module. The inputs of PV module are temperature from 5- 100 °C and irradiance from 100 to 1000 W/m2. The DC-DC buck converter then feed with the PV module output to step down and regulate the output of PV with 0.4 of duty cycle to the compatible value for batteries or dc appliances. The output of PV cells varies with the temperature of PV cells and irradiance. The maximum power of PV module gained when the cell temperature is 25 °C and the irradiance is 1000 W/m2. The DC-DC buck converter step down the voltage output from PV module and the efficiency is around 34%.